SMOKING THE ENVIRONMENT AND HUMAN RIGHTS - Emrah AKYÜZ (Fırat University, 2019)
Environmental pollution is one of the most important issues facing the world’s population in the 21st century. As a result of environmental issues, millions of people are dying and contracting serious illnesses, and others are at risk of losing their basic human rights and freedoms. The severity of enviromental problems is accepted and dates to the period of human history since the Industrial Revolution. After the Industrial Revolution people’s life styles and consumption habits changed significanlty. In order to meet our needs and to live a more comfortable life, humankind had started to destroy the nature. Here it is important to emphasise that people are risking the stability of the environment not only to meet their basic needs but also in pursuit of hobbies and habits. Smoking is a unique example, which directly shows how poeple pollute the environment to satisfy their habits. The key aim of this research is to examine whether or not smoking constitutes a human rights violation in the context of the right to a clean and safe environment.